Bio-analytical method development and validation of Rasagiline by high performance liquid chromatography tandem mass spectrometry detection and its application to pharmacokinetic study - Ravi Kumar Konda; Babu Rao Chandu; B.R. Challa; Chandrasekhar B. Kothapalli (Elsevier, 2012)
The most suitable bio-analytical method based on liquidâliquid extraction has been developed and validated for quantification of Rasagiline in human plasma. Rasagiline-13C3 mesylate was used as an internal standard for Rasagiline. Zorbax Eclipse Plus C18 (2.1Â mmÃ50Â mm, 3.5Â Î¼m) column provided chromatographic separation of analyte followed by detection with mass spectrometry. The method involved simple isocratic chromatographic condition and mass spectrometric detection in the positive ionization mode using an API-4000 system. The total run time was 3.0Â min. The proposed method has been validated with the linear range of 5â12000Â pg/mL for Rasagiline. The intra-run and inter-run precision values were within 1.3%â2.9% and 1.6%â2.2% respectively for Rasagiline. The overall recovery for Rasagiline and Rasagiline-13C3 mesylate analog was 96.9% and 96.7% respectively. This validated method was successfully applied to the bioequivalence and pharmacokinetic study of human volunteers under fasting condition. Keywords: High performance liquid chromatography, Mass spectrometry, Rasagiline, Liquidâliquid extraction